Human Nature and the Universality of the Shari’ah: Fitrah and Maqasid Al-Shari’ah in the Works of Shah Wali Allah and Ibn ’Ashur - El-Mesawi, Mohamed El-Tahir (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Human Nature and the Universality of the Shari’ah: Fitrah and Maqasid Al-Shari’ah in the Works of Shah Wali Allah and Ibn ’Ashur